THE LEGALITY OF INTERRELIGIOUS MARRIAGE IN THE PERSPECTIVE OF ISLAMIC LAW AND INDONESIAN POSITIVE LAW - Muchammad Ichsan (Profetika: Jurnal Studi Islam, 2016)
This study aims at examining the legality of interreligious marriage according to Islamic law and Indonesian positive law. To reach the goal set by this research, a descriptive method is used in the writing while an analytical method is employed to scrutinize the relevant problems. This study finds that interreligious marriage has spread widely among Indonesians that it has now become a phenomenon. However, Islam does not recognize a Muslim woman's marriage unless she is married by a man belonging to the same religion, i.e. a Muslim. A Muslim man is not permitted to marry a mushrik (polytheist) woman. It is lawful for him to marry a woman from the Ahlul Kitaab (Jews and Christians), but Indonesian ulemas prohibit such a marriage as well because of the negative outcomes. Meanwhile, the 1974 Indonesian Marriage Law fails to address the issue of interreligious marriage in a clear manner. This brings forth at least three interpretations: firstly, the law does not regulate interreligious marriage at all; secondly, the law allows it; and thirdly, the law denies it. Through an analysis, the last interpretation is found to have stronger reasons than the others.  Penelitian ini bertujuan untuk menguji legalitas pernikahan antaragama menurut hukum Islam dan hukum positif Indonesia. Agar tercapai tujuan yang diinginkan, maka penelitian ini menggunakan metode deskriptif untuk menganalisis masalah yang sedang diteliti. Studi ini menemukan bahwa pernikahan antaragama telah menyebar luas di kalangan masyarakat Indonesia yang kini telah menjadi fenomena. Namun, Islam tidak mengenali pernikahan wanita Muslim kecuali jika dia menikah dengan pria yang memiliki agama yang sama, yaitu seorang Muslim. Seorang pria Muslim tidak diizinkan untuk menikahi wanita musyrik (politeis). Dan halal baginya untuk menikahi wanita dari Ahlul Kitaab (Yahudi dan Kristen), namun sebagian ulama Indonesia tetap melarang pernikahan semacam ini, karena beberapa alasan. Sementara itu, Undang-Undang Perkawinan Indonesia 1974 gagal menangani masalah pernikahan antaragama dengan cara yang jelas. Ini setidaknya menghasilkan tiga interpretasi: pertama, hukum sama sekali tidak mengatur pernikahan antaragama; Kedua, hukum mengizinkannya; Ketiga, undang-undang tersebut menolaknya. Melalui sebuah analisis tersebut di atas, disimpulkan bahwa jenis interpretasi yang terakhir ditemukan memiliki alasan yang lebih kuat daripada alasan yang lainnya.